Gender Matters in the Call Center Industry: A Review of Literature on the Effects of Call Center Work on Women - Cabarrubias, Leavides G. Domingo (Review of Women's Studies; Vol 21 No 2 (2011): Review of Women's Studies Volume XXI, Number 2 (July-December 2011))
The dramatic increase in call center jobs has spawned numerous research about this industry and its effects on workers around the world. This review of literature covers some of these works and examines whether the gender-differentiated impact of call center work has been adequately explored. While men and women may be similarly exposed to the same stressful working environment and demanding work load, the effects are not necessarily the same. Earlier studies parenthetically cite specific effects of call center work on women such as health problems of pregnant and lactating mothers, safety concerns of women working at night, as well as conflicts between working hours and the demands of task performance and domestic and family responsibilities. A highly stressful job, coupled with graveyard shifts and unpredictable schedules, can have significant effects on women’s traditional caring roles at home as well as on the gender division of labor within the household.